Frequency of Bullying Behaviours in Secondary Schools in Cluj-Napoca - Ioana Elena BELDEAN-GALEA (Applied Medical Informatics, 2010)
“Bullying” is generally considered to be a specific form of aggressive behaviour. The aim of this paper is the investigation of gender and age-related bully and victim incidence in Cluj-Napoca secondary schools. A survey on bullying was completed by 264 students (141 girls and 123 boys; 112 students from grades 5-6 and 152 students from grades 7-8) with an age range between 10 and 14 years old. From the entire sample, results showed that 3.8% of the students bullied others once a week or more during the previous 3 months and 40.5% had been frequently bullied by other students once a week or more often during the previous 3 months. Considering the gender differences, girls showed a bullying behaviour more frequently than boys.